Plasmin/plasminogen is essential for the healing of tympanic membrane perforations - Li, Jinan; Eriksson, Per-Olof; Hansson, Annika; Hellström, Sten; Ny, Tor (Thrombosis and Haemostasis, 2006)
Plasminogen has been proposed to play an important role in different tissue remodeling processes such as wound healing and tissue regeneration after injuries. The healing of tympanic membrane perforations is a well-organized chain of inflammatory events, with an initial invasion of inflammatory cells followed by reparative and restoration phases. Here we show that the healing of tympanic membrane perforations is completely arrested in plasminogen-deficient mice, with no signs of any healing even 143 days after perforation. Inflammatory cells were recruited to the wounded area, but there were no signs of tissue debridement. In addition, removal of fibrin, keratinocyte migration and in-growth of connective tissue were impaired. This contrasts with skin wound healing, where studies have shown that, although the healing process is delayed, it reaches completion in all plasminogen-deficient mice. Our finding that keratinocyte migration and re-epithelialization were completely arrested in plasminogen-deficient mice indicates that plasminogen/plasmin plays a more profound role in the healing of tympanic membrane perforations than in the healing of other epithelial wounds.
Keywords: Plasmin; wound healing; tympanic membrane; inflammation; neutrophils